Relevansi Nilai Earning per Share, Price Book Value, Cash Flow, Current Ratio dan Harga Saham: Return on Asset Sebagai Pemoderasi - Arry Eksandy; Dirvi Surya Abbas (Jurnal Akuntansi)
The purpose of this study is to determine the results of Earnings Per Share, Book Value Equity, Operating Cash Flow, Investment Cash Flow, Funding Cash Flow, Current Ratio, Asset Returns and Asset Returns moderate Operating Cash Flow to Share Prices in manufacturing companies found in Indonesia stock exchange. This research population publishes manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria the number of samples obtained by 9 companies. The type of data used in this study is secondary data using panel data regression analysis methods. The results showed that Earnings Per Share and Book Value of Equity showed a positive effect on the Share Price, then, Funding Cash Flow, Return on Assets and Return on Assets moderate the Operating Cash Flow negatively evaluating the Stock Price. Whereas Operating Cash Flow, Investment Cash Flow, and Current Ratio do not affect the stock price.